1978
DOI: 10.1530/acta.0.0870434
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Inhibin From Bull Seminal Plasma

Abstract: A simple, short procedure for the isolation of inhibin from bull seminal plasma has been described. Following conversion of the seminal plasma into acetone powder, it was subjected to gel filtration on Sephadex G-100 using 4 m urea\p=m-\0.05 m sodium acetate buffer pH 4.0 as the eluent. Further purification of the active fraction was achieved by 'straight elution analysis' using CM-cellulose. The final preparation (UX) has been shown to reduce the response of immature rat ovaries to human chorionic gonadotroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

1979
1979
1988
1988

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…As yet, we cannot be certain that the gonadotrophin-inhibiting activity observed here is the same as the "bSP-inhibin" described and isolated by Chari et al (1978).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…As yet, we cannot be certain that the gonadotrophin-inhibiting activity observed here is the same as the "bSP-inhibin" described and isolated by Chari et al (1978).…”
Section: Discussionmentioning
confidence: 50%
“…This gonado¬ trophin-inhibiting activity has some properties in common with the FSH-suppressing activity in bull seminal plasma described by Franchimont et al (1975a) and recently purified and called "bSP-inhibin" by Chari, Duraiswami & Franchimont (1978 Such variation may be due to differences in the methods used to detect FSH and LH suppres¬ sion, or in the material under study. Chari et al (1978) have shown that intravenous injection of freshly prepared "bSP-inhibin" into acutely castrated 35-day-old rats caused suppression of FSH alone, while material which had been stored at -20°C for 6 weeks suppressed both FSH and LH. The seminal plasma samples used in the present study were stored at -20°C for more than 6 weeks before they were used.…”
Section: Discussionmentioning
confidence: 68%
“…FSH inhibiting substances have been detected in numerous gonadal tissues and fluids of mammals, such as rete testis fluid (4,5), seminal plasma (5)(6)(7)(8), ovarian follicular fluid (9)(10)(11)(12)(13)(14)(15), and media of cultured Sertoli (16,17) and granulosa cells (18). An inhibin-like peptide containing 31 amino acids (a-inhibin-31) was first synthesized and shown to be biologically active in vivo and in vitro (8,19).…”
mentioning
confidence: 99%
“…Besides differences in the acid-base and molecular weight characteristics, contradictory evi dence has been reported concerning the gly coprotein nature of inhibin. On one hand it has been claimed that relatively pure inhibin preparations obtained from seminal plasma or testicular extracts contain no sialic acid or other carbohydrate residues and that semipure material obtained from extracts of ham ster ovaries does not bind to concanavalin ASepharose [Chari et al, 1978;Thakur et al, 1978;Chappel ct al., 1979;Sairam, 1981]. On the other hand, some investigators have shown that neuraminidase treatment of in hibin abolishes its biological activity and that inhibin does bind to concanavalin A-Sepharose [Setchell et al, 1977;de Jong et al, 1981;Franchimonl et al, 1982].…”
Section: Introductionmentioning
confidence: 99%